2016
DOI: 10.1002/aur.1666
|View full text |Cite
|
Sign up to set email alerts
|

High autistic trait individuals do not modulate gaze behaviour in response to social presence but look away more when actively engaged in an interaction

Abstract: Autism is characterised by difficulties in social functioning, notably in interactions with other people. Yet, most studies addressing social difficulties have used static images or, at best, videos of social stimuli, with no scope for real interaction. Here, we study one crucial aspect of social interactions—gaze behaviour—in an interactive setting. First, typical individuals were shown videos of an experimenter and, by means of a deception procedure, were either led to believe that the experimenter was prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
4
33
2
Order By: Relevance
“…Between 6 months and 3–4 years of age, however, children’ attentional responses become more readily engaged by a sophisticated understanding of the social nature of environmental affordances, gaze–object intentional relationship, as well as an understanding of the communicative intent conveyed by eye contact, with these abilities maturing with the full development of mentalizing abilities around 4 years of age . Clinical evidence also supports dissociations between perceptual and interpretive analyses, as individuals with autism are often found to display relatively intact attentional responses to social stimuli like faces and facial features, but show altered sensitivity to the social function of those cues in signaling agents’ interest, desires, and/or intentions toward objects in the environment . In contrast, the links between attentional and evaluative processes are well preserved phylogenetically and appear to emerge early in human development.…”
Section: The Relationship Between the Three Core Processesmentioning
confidence: 98%
“…Between 6 months and 3–4 years of age, however, children’ attentional responses become more readily engaged by a sophisticated understanding of the social nature of environmental affordances, gaze–object intentional relationship, as well as an understanding of the communicative intent conveyed by eye contact, with these abilities maturing with the full development of mentalizing abilities around 4 years of age . Clinical evidence also supports dissociations between perceptual and interpretive analyses, as individuals with autism are often found to display relatively intact attentional responses to social stimuli like faces and facial features, but show altered sensitivity to the social function of those cues in signaling agents’ interest, desires, and/or intentions toward objects in the environment . In contrast, the links between attentional and evaluative processes are well preserved phylogenetically and appear to emerge early in human development.…”
Section: The Relationship Between the Three Core Processesmentioning
confidence: 98%
“…Research on Autism Spectrum Disorder (ASD) has shown that individuals with ASD tend to pay less attention to others' expressions of distress 31 , and gaze less into another's eyes 32,33 . Similarly, research on typically developed participants (without ASD diagnosis) showed that those with low AQ scores looked more at the other in real-time social interactions than those with high AQ scores 34 . Given these findings, a lower-AQ individual might attend more to another's reactions than a higher-AQ individual.…”
Section: Discussionmentioning
confidence: 93%
“…Our paradigm suggests that patterns of gaze behavior in ASD individuals are dependent on the social situation, rather than just the social stimulus or presence of another person, and that reduced looking at another person in individuals with ASD in an interactive setting may be driven by factors associated with active engagement (von dem Hagen et al 2016). Of course, this paradigm would not be effective with infants as it requires verbal report, but could be adapted to some extent for young children, as well as for non-verbal individuals using augmentative support.…”
Section: Discussionmentioning
confidence: 99%